Causality Testing of Industrialisation, Trade Openness and Carbon Dioxide Emissions for South Africa - Tala, Lavisa (International Journal of Energy Economics and Policy, 2025)
This study test causality between industrialisation, trade openness and carbon emissions and examined shocks from innovations for the period from 1990 to 2023. Results from Johansen Cointegration test showed presence of long-run association among industrialisation, trade openness and carbon emissions. Empirical results obtained from DOLS estimator indicated that industrialisation is instrumental in lowering carbon emissions. While trade openness promotes carbon dioxide emissions, suggesting high carbon content of international trade. Granger causality reveals that industrialisation Granger cause trade openness, whereas industrialisation and CO2 jointly cause trade. Variance decomposition suggested unidirectional tendencies from LOC2 and TRADE to LINDUS. Impulse response results indicate bi-directional Granger causality tendency between TRADE and carbon emissions, and one-way causal link from industrialisation to trade. The study results indicate that industrialisation is a contributor to finding sustainable solution for carbon free economy. The outcome underscore important role of industrialisation in driving green investment and development of green technology. Government should allocate scarce resources to the industrial sector for innovation and development of domestic green technologies. Global development of green technologies and transfer is required for effective reduction of CO2 emitted during trade related production and transportation. To promote environmentally friendly trade, reduction of trade barriers on green technologies is recommended.